2002
DOI: 10.1038/nm0102-41
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor receptor and ADAM10 mediate responses to Staphylococcus aureus in epithelial cells

Abstract: In the lungs of cystic fibrosis patients, overproduction of mucus leads to morbidity and mortality by obstructing airflow and shielding bacteria from antibiotics. Here we demonstrate that overproduction of mucus is a direct result of the activation of mucin gene expression by Gram-positive bacteria. Bacterial lipoteichoic acid activates the platelet-activating factor receptor, which is G protein-coupled. This results in activation of a disintegrin and metalloproteinase (ADAM10), kuzbanian, cleavage of pro hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
279
3
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(301 citation statements)
references
References 25 publications
10
279
3
9
Order By: Relevance
“…Hypothesized that the TLR2-MyD88-NF-κB pathway plays a crucial role in PGNinduced MUC5AC expression (Thai et al, 2008). Interestingly, S. pyogenes PGN could not induce MUC2 gene expression, whereas lipoteichoic acid (LTA) was able to do so in HM3 cells (Lemjabbar et al, 2002). The discrepancy of PGN signaling in S. aureus versus S. pyogenes may derive from the difference in pathogeneses of these two bacteria in the airway.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothesized that the TLR2-MyD88-NF-κB pathway plays a crucial role in PGNinduced MUC5AC expression (Thai et al, 2008). Interestingly, S. pyogenes PGN could not induce MUC2 gene expression, whereas lipoteichoic acid (LTA) was able to do so in HM3 cells (Lemjabbar et al, 2002). The discrepancy of PGN signaling in S. aureus versus S. pyogenes may derive from the difference in pathogeneses of these two bacteria in the airway.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB activation in airway epithelial cells is a common event during inflammatory conditions. Utilizing bacterial extracts from P. aeruginosa and Staphylococcus aureus, investigators found that that LPS and LTA can induce MUC2 expression in the colon epithelial cell line HM3 (32,33). Further studies showed that both signaled through the activation of Ras-MEK1/2-ERK1/2 pathways.…”
Section: Muc2 Expression Regulated By Mitogen-activated Protein Kinasmentioning
confidence: 99%
“…LTA does not act directly on Ras but instead first activates ADAM10, a matrix metalloprotease (MMP), to cleave membrane-bound pro-EGF (epidermal growth factor) to release free EGF ligands. These EGF ligands then bind to EGFR, which then activates RAS-MEK1/2-ERK1/2, as does LPS, to cause NF-κB activation of MUC2 transcription (33). P. aeruginosa also has a protein called flagellin that can activate airway epithelial cells and MUC2 expression (34).…”
Section: Muc2 Expression Regulated By Mitogen-activated Protein Kinasmentioning
confidence: 99%
“…Mucin concentration in broncoalveolar lavage is increased in response to LPS and flagella, and MUC5A gene expression is upregulated by LPS and Gram-positive and Gram-negative bacteria 78 as well as pro-inflammatory chemokines and cytokines expressed by airway epithelial cells. 79 MUC2 expression is also increased in response to P. aeruginosa LPS and flagellin, 80,81 S. aureus lipoteichoic acid 82 and H. influenzae 83 by signaling cascades that share common elements with those induced by TLRs.…”
Section: Airway Epithelial Cell Responses To Bacteriamentioning
confidence: 99%